Comparative analysis between tensile adhesion and compressive strength in mortars produced with expanded vermiculite - Affonso, Stella Bruna Ananias; Alves, Edson; Azambuja, Maximiliano dos Anjos (National Journal of City Management, 2025)
In the construction industry, the performance of building elements is a pertinent topic for scientific research. Sustainability and concern for non-renewable natural resources have stimulated the search for alternative materials that have the potential to improve the properties of cement mortars. Although it is a material that is still rarely used as an aggregate in mortars, expanded vermiculite has interesting properties, with the potential to replace natural sand, reducing the environmental impact caused by its extraction. The aim of this study was to analyze, based on physical and mechanical characteristics, the reduction in environmental impact caused by replacing natural sand with expanded vermiculite as an aggregate in coating mortars. In this study, we analyzed the compressive strength and tensile bond strength of coating mortars produced from a 1:1:6 mix by volume and with 10, 20, 30, 40 and 50% replacement of natural aggregate with expanded vermiculite, comparing them with a reference mix. The experimental stage consisted of characterizing the aggregates, making the mortars and testing them in the fresh and hardened state. According to NBR 13281-1 (ABNT, 2023), the mixtures can be classified in terms of compressive strength as P3 (AN100, VE10, VE40 and VE50, with strengths between 2.5 and 4.5 MPa) and P4 (VE20 and VE30, with strengths between 4.0 and 6.5 MPa). Based on the same standard, the mixtures can be classified in terms of tensile bond strength as RA1 (AN100, VE40 and VE50, for strength greater than or equal to 0.2 MPa) and RA2 (VE10, VE20 and VE30, for strength greater than or equal to 0.3 MPa). It should be noted that the results for the intermediate traits VE20 and VE30, with compressive strengths between 4.0 and 6.5 MPa and tensile bond strengths greater than or equal to 0.3 MPa, can be classified as P4 and RA2 respectively. All the mixes complied with NBR 13749 (ABNT, 2013), which stipulates minimum values of 0.20 MPa for internal walls and 0.30 MPa for external walls. VE10, VE20 and VE30 were suitable for external cladding, while VE40 and VE50 were suitable for internal cladding. In these last two cases, the mixture stands out for meeting the standard and causing less environmental impact.
Keywords: Mechanical properties; Expanded vermiculite; Sustainability